Changes in Women’s Representations in Turkish Cinema from the 1980s to the Early 1990s - Fatma Özen (CINEJ Cinema Journal, 2021)
This article focuses on the representations of women alongside the social and historical background of Turkish cinema from the 1980s through the early 1990s. In the following section, I articulate the political events in the 1980s - the early1990s and its impacts on Turkish society and cinema. I delve into the modernist representations of women in the 1980s cinema to analyze women’s gender codes (based on social/cultural and cinematic codes). Finally, in the last section, I examine Atıf Yılmaz’s cinematic images of women in his films and analyze two of his films A Sip of Love (1984) and The Night, Angel and Our Gang (1994) in terms of gender codes.